A Review of Measures and Indicators for Assessing the Relationship Between Women’s Empowerment and Nutrition - Olney, Deanna K.; Shapleigh, S. (CGIAR GENDER Impact Platform, 2022)
In this review we sought to understand how the relationship between women’s empowerment and women’s and children’s diet and nutrition outcomes have been conceptualized and studied. Generalizations about the relationships between “women’s empowerment” and “nutrition” abound, with little understanding of what is meant by either of these general categories. The frameworks that are used to illustrate these relationships may be too general to be useful in understanding the relationship between a complex construct like women’s empowerment, and behavioral (e.g., diet diversity) and biological (e.g., stunting) outcomes that have both shared and different causes. In this paper we discuss the different women’s empowerment and diet and nutrition tools that have been used when assessing the relationship between the two, and assess how the different combinations of empowerment and diet/nutrition have been studied. Within five broad categories of empowerment, we provide summaries of the findings from the included studies. Considering the results of this review, we highlight gaps in how these relationships are conceptualized and measured, and suggest ways to deepen understanding of these relationships. This paper can be informative for researchers who want to know how the relationships between women’s empowerment and nutrition have been generally assessed, and for program implementers who are interested in understanding what components of women’s empowerment may be more promising in influencing diet and nutrition outcomes among women and children.